العوامل المؤثرة في الاغتراب الوظيفي لدى العاملات في مؤسسة الصندوق الوطني للتأمينات الاجتماعية بالاغواط - نعيجات خديجة; بلحبيب نسرين; فرحات احميدة (جامعة عمار ثليجي الاغواط, 2022)
This study aims to find out the the affecting factors in job alienation among female employess of national social insurance fund for employed workers Laghouat section, by building an applicable model, based on two basic variables represented in job alienation as a dependent variable, the affecting factors as an independent variable with its dimensions (the external affecting factors, the subjuctive affecting factors). To achieve the study goal; A questionnaire was developed for the purpose of collecting information and data from the study sample, which were 64 female employees. using (SEM) and SmartPLS3 software to analyze the various links between the studied variables. The study concluded that there is a statistically significant effect of the affecting factors on job alienation among female employess in the institution host of the study at the level of morale at 0,05. he study also found, there are no statistically significant differences at the same the level of significance and the same variables as the model of study personal data of the sample members examined representing: (age, academic level, martial status, years of service, and functional level).